2008
DOI: 10.1080/02640410701446919
|View full text |Cite
|
Sign up to set email alerts
|

State anxiety and visual attention: The role of the quiet eye period in aiming to a far target

Abstract: In this study, we examined how individuals controlled their gaze behaviour during execution of a far aiming task and whether the functional relationship between perception and action was disrupted by increased anxiety. Twenty participants were trained on a simulated archery task, using a joystick to aim and shoot arrows at the target, and then competed in two counterbalanced experimental conditions designed to manipulate the anxiety they experienced. The specific gaze behaviour measured was the duration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
148
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(164 citation statements)
references
References 31 publications
12
148
0
1
Order By: Relevance
“…The behaviors have been reported to be affected by state anxiety, with a shift towards a more stimulus-driven control of attention (cf. Wilson et al, 2008). Similarly, a prolonged QE Our findings support earlier reports where increases in anxiety have been shown to negatively affect QE characteristics.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The behaviors have been reported to be affected by state anxiety, with a shift towards a more stimulus-driven control of attention (cf. Wilson et al, 2008). Similarly, a prolonged QE Our findings support earlier reports where increases in anxiety have been shown to negatively affect QE characteristics.…”
Section: Discussionsupporting
confidence: 82%
“…However, in studies investigating the effects of anxiety on QE characteristics there have been consistent results indicating a decrement in performance as a result of a reduction in QE duration (Behan & Wilson, 2008;Wilson et al, 2009a;Vickers & Williams, 2007). In the current study, a significant difference in performance outcome was observed across the two anxiety conditions with reduced performance scores being evident in the high anxiety condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have found supporting evidence for the predictions of ACT on gaze behavior [4,5,6,7,8]. Anxiety has been shown to increase the frequency of fixations on goal-irrelevant stimuli [8] and to reduce the duration of ordinarily long target-focused fixations [5,9,7].…”
Section: Introductionmentioning
confidence: 99%